Moral development through a sports and values program in adult students with intellectual disabilities - Sánchez-Romero, Elisa Isabel; Vilchez, María Pilar; Iniesta-Sepúlveda, Marina; De Francisco, Cristina (Anales de Psicología / Annals of Psychology, 2021)
The aim of this study was to increase moral development of the students with intellectual disabilities, through an intervention with values learning and adapted sports. The program was developed in a training course for Social and Labor insertion of People with Intellectual Disability. The sample consisted of 37 students of three consecutive promotions (n1 = 11; n2 = 12; n3 = 14), aged from 19 to 37 years (M = 24.49 ± 4.22). Instrument used was the Spanish version of the Moral Competence Test adapted to intellectual disability (MCT) which measures the two components of moral development through two scores: moral competence and moral orientations/preferences. A quasi-experimental recurrent institutional cycle cohort design was planned. This design involved three cohorts, evaluated in three consecutive years. In addition, to ensure the equivalence of the groups, a study was carried out on the influence of sociodemographic and clinical variables in the change of students’ moral competence, through a prospective ex post facto single group design. The results showed an improvement in two components of moral development, with statistically significant differences in stage 4 of moral orientations/preferences.